Large nitric acid particles at the top of an Arctic stratospheric cloud - Deshler, Terry; Larsen, Niels; Weissner, Christoph; Schreiner, Jochen; Mauersberger, Konrad; Cairo, Francesco; Adriani, Alberto; Di Donfrancesco, Guido; Ovarlez, Joelle; Ovarlez, Henri; Blum, Ulrich; Fricke, K. H.; et al. (Journal of Geophysical Research, 2003)
International audience In early December 2001, balloon-borne in situ measurements of particle composition, size, number, phase, and backscatter were completed in an Arctic stratospheric cloud composed of three distinct layers between 22 and 26 km. Below 24.5 km, liquid solution droplets of water, nitric acid, and sulfuric acid and a thin ice layer were observed. Above this layer the particles were primarily solid nitric acid trihydrate. Just above 26 km, at cloud top, where temperatures were near or above the equilibrium temperature for nitric acid trihydrate, there was a thin layer of solid particles narrowly distributed around a radius of 2.0 μm at concentrations of <0.001 cm -3 . Lidar backscatter and particle phase measurements approximately 200 km upwind of the in situ measurements indicate a similar vertical structure for the cloud. These in situ measurements represent, to our knowledge, the most comprehensive in situ observations of all phases of polar stratospheric cloud particles, while the large particles at cloud top have not been previously observed and may have implications for producing particles large enough to remove reactive nitrogen from the polar stratosphere.